2018
DOI: 10.1016/j.bbi.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin suppresses neuroinflammation and improves neurological recovery via CaMKK2/AMPK/Nrf2 pathway after germinal matrix hemorrhage in neonatal rats

Abstract: Chemerin, an adipokine, has been reported to reduce the production of pro-inflammatory cytokines and neutrophil infiltration. This study investigated the role of Chemerin and its natural receptor, ChemR23, as well as its downstream mediator calmodulin-dependent protein kinase kinase 2 (CAMKK2)/adenosine monophosphate-activated protein kinase (AMPK) /Nuclear factor erythroid 2-related factor 2 (Nrf2) following germinal matrix hemorrhage (GMH) in neonatal rats, with a specific focus on inflammation. GMH was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 55 publications
(100 reference statements)
3
74
0
Order By: Relevance
“…Similar to M1 microglia, besides from ischemic stroke, M2 microglia activation occurs in numerous other types of neurological disease; for example, in both spinal cord injury and intracerebral hemorrhage mouse models, M2 microglia were identified to be activated, which released anti-inflammatory cytokines downstream of caMP response element-binding protein (creB)-associated signaling pathways (56,57). in neonatal germinal matrix hemorrhage rats, Rh-Chemerin promoted the accumulation and proliferation of M2 microglia in periventricular regions and suppressed the inflammatory response through nuclear factor erythroid 2-related factor 2 (nrf2)-associated signaling pathways (58). Previous studies demonstrated that M2 microglia activation can also promote brain tissue repair in other neurological diseases (56)(57)(58).…”
Section: Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to M1 microglia, besides from ischemic stroke, M2 microglia activation occurs in numerous other types of neurological disease; for example, in both spinal cord injury and intracerebral hemorrhage mouse models, M2 microglia were identified to be activated, which released anti-inflammatory cytokines downstream of caMP response element-binding protein (creB)-associated signaling pathways (56,57). in neonatal germinal matrix hemorrhage rats, Rh-Chemerin promoted the accumulation and proliferation of M2 microglia in periventricular regions and suppressed the inflammatory response through nuclear factor erythroid 2-related factor 2 (nrf2)-associated signaling pathways (58). Previous studies demonstrated that M2 microglia activation can also promote brain tissue repair in other neurological diseases (56)(57)(58).…”
Section: Microgliamentioning
confidence: 99%
“…in neonatal germinal matrix hemorrhage rats, Rh-Chemerin promoted the accumulation and proliferation of M2 microglia in periventricular regions and suppressed the inflammatory response through nuclear factor erythroid 2-related factor 2 (nrf2)-associated signaling pathways (58). Previous studies demonstrated that M2 microglia activation can also promote brain tissue repair in other neurological diseases (56)(57)(58).…”
Section: Microgliamentioning
confidence: 99%
“…[47][48][49] Other studies have suggested that chemerin may play an anti-inflammatory role. 14,50,51) The underlying mechanisms of the function of C9 in cognition and AD are still unclear. We hypothesize that it is closely related to the inflammation status in the brain.…”
Section: V) On Locomotor Behaviour In Micementioning
confidence: 99%
“…Intracerebroventricular drug administration was performed as previously described (15). Briefly, rats were placed in a stereotaxic apparatus under 2.5% isoflurane stereotactic anesthesia.…”
Section: Gmh Model and Experimental Protocolmentioning
confidence: 99%